Peripheral Ameloblastoma of the Gingiva - Zaffar, Ghazal; Khalid, Ahmareen (International Journal of Pathology, 2018)
Peripheral Ameloblastoma is a benign and rare odentogenic tumor with a slow growing clinical course. It is an asymptomatic lesion and grows as a swelling. We report a case of Peripheral ameloblastoma in the gingiva within the oral cavity which was removed and on histopathological evaluation revealed predominantly plexiform architectural pattern formed by epithelial cells with characteristic reverse polarity.